Nikumoowina [electronic resource] : hymns translated by Mrs. Hunter into the language of the Cree Indians, of the Diocese of Rupert's Land, North-West America. - Hunter, Jean, b. 1822. (London : Society for Promoting Christian Knowledge, 1886)
Electronic reproduction. Mode of access: Internet. 44